(untitled) (Experimental biology, 2017)
In work influence synthetic regulators of growth (Т-10, Т-10 ’, Т-10 ") on salt-endurance of spring wheat of a grade of "Zhenis"is studied. Influence of regulators of growth on germination, growth and and development of wheat in the conditions of salinization.